Spin-reorientation transition of epitaxial Cu/Ni/Cu (001) structure - Hwang, HM; Park, JC; You, DG; Park, HS; Jeong, K; Lee, J; Kim, TG; Song, JH (AMER INST PHYSICS, 2003)
We have studied the spin-reorientation transition of Cu/Ni/Cu (001) system by measuring the strain, coercive field, and magnetic anisotropy of epitaxial Cu/Ni/Cu (001) films. We found that the critical thickness (t(c)) of Ni for the coherent growth of Ni on Cu is below 25 Angstrom and does not occur at the peak in the effective magnetic anisotropy constant (K-eff) versus 1/t curve, where t is the Ni thickness. The 60-Angstrom Ni film, which is highly strained and shows out-of-plane magnetization, has been irradiated by 1-MeV C ions. After irradiation, the magnetization lies in the plane and the strain in the Ni film is almost released. This shows the close relationship between strain and out-of-plane magnetization in this system. (C) 2003 American Institute of Physics.
Keywords: ION-BEAM MODIFICATION; MAGNETIC-ANISOTROPY; MAGNETOELASTIC ANISOTROPY; FERROMAGNETIC-RESONANCE; ULTRATHIN FILMS; FE(100) FILMS; CO LAYER; MULTILAYERS; CU(100)/SI(100); SANDWICHES